Pembelajaran Imla’ Melalui Media Whatsapp Di Kelas III MI Cemorokandang - M. Afief Akbari; Muassomah Muassomah (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
This study discusses: Imla' Learning & the material exercises are carried out through Whatsapp media in class III MI Cemorokandang, and the impact of Imla' learning carried out. While the research method that researchers use in this study is a descriptive qualitative research method. Then after the data is collected, data analysis is carried out by: data reduction, data presentation and drawing conclusions. In this study, it can be seen that the stages of implementing Imla' learning in third grade students begin with greetings, prayers, then the teacher sends the material to be discussed to the group, 10 to 15 minutes after the material is distributed, the teacher and students can discuss or ask questions about the material that has been discussed. As explained earlier, the teacher then sends a text message or voice note to the group asking the students to do the exercises given, and in closing, they can re-deliver the material that has been discussed at a glance. The answer from the students or teachers of the Arabic language subject related to the Imla 'learning that has been carried out is that related to the practice of pronunciation & writing, giving examples and others is considered satisfactory, it's just that when giving assignments it needs to be explained as clearly as possible